Analysis Of The Effect Of Socio-Political Factors On Self-Management And Family Care Abilities In Prevention Of Severity Effort In Patient With Coronary Heart Disease - Fitriah, Fitriah; Rodiyatun, Rodiyatun; Suryaningsih, Suryaningsih; Haris, Mustofa (NHM PRESS, 2023)
Coronary heart disease is the biggest killer responsible for 16% of total deaths worldwide. The death rate due to coronary heart disease in Indonesia is 12.9% percent from total cause of death in Indonesia. Because of the high mortality from the severity of coronary heart disease, effective severity prevention methods are needed to reduce the mortality rate from coronary heart disease. The purpose of this research is to analyze the effect of social factors, political factors and family characteristics on self-management and family care abilities in prevention of severity effort in coronary heart disease. The research design was analytical observational with Cross Sectional approach. Exogenous variables social factors and political factors. Endogenous variables self-management, family care abilities, prevention of severity in coronary heart disease. The population was all patients with coronary heart disease at Anna Medika Madura General Hospital with total sample 130 respondents. Sampling using convenience sampling and instrument using questionnaires with statistical test partial least square (PLS) with α > 0.5. The results of PLS showed that exogenous variables social factors and political factors had significant influence on self-management. Self-management affects the ability to care for family. Family care abilities affects the prevention of severity in coronary heart disease. The new findings of this study are self-management and family care abilities in prevention of severity effort of coronary heart disease can be formed through social factors and political factors